2017
DOI: 10.1016/j.jacc.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Chamber Pacing With Closed Loop Stimulation in Recurrent Reflex Vasovagal Syncope

Abstract: DDD-CLS pacing significantly reduced syncope burden and time to first recurrence by 7-fold, prolonging time to first syncope recurrence in patients age ≥40 years with head-up tilt test-induced vasovagal syncope compared with sham pacing. (Closed Loop Stimulation for Neuromediated Syncope [SPAIN Study]; NCT01621464).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 18 publications
1
58
0
4
Order By: Relevance
“…Mostly, drug‐based or change‐of‐lifestyle‐options are effectively preventing syncope. The use of cardiac pacemakers (PM) remains a controversial topic and should only be considered in very severe cases . This is reflected by a class IIb indication in current adult as well as pediatric guidelines .…”
Section: Introductionmentioning
confidence: 99%
“…Mostly, drug‐based or change‐of‐lifestyle‐options are effectively preventing syncope. The use of cardiac pacemakers (PM) remains a controversial topic and should only be considered in very severe cases . This is reflected by a class IIb indication in current adult as well as pediatric guidelines .…”
Section: Introductionmentioning
confidence: 99%
“…When pooling data from all the trials, a 63% reduction in syncope recurrence was found (RR: 0.37; 95% CI: 0.14‐0.98; I 2 = 67%) (Figure ). Subgroup analysis (Figure ) by follow‐up was not associated with a statistically significant subgroup effect ( P = .14) [>12 months (RR: 0.62; 95% CI: 0.22‐1.71, I 2 = 61%); ≤12months (RR: 0.14; 95% CI: 0.02‐0.77, I 2 = 38%)]. A subgroup effect ( P = 0.07) was found when analysing blinding.…”
Section: Resultsmentioning
confidence: 95%
“…Number of participants varied from 26 to 100 patients. Follow‐up was as short as 11 months to a maximum of 24 months . All studies enrolled patients with cardioinhibitory syncope detected through TTT except one, which used ILR .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the previous studies have small sample sizes with no more than 50 subjects included. Recently, more studies have shown superior efficacy of CLS compared to conventional pacing . In this systematic review and meta‐analysis, we investigated the impact of CLS implantation on reduction in recurrent VVS events.…”
Section: Introductionmentioning
confidence: 99%